2018
DOI: 10.1002/etc.4275
|View full text |Cite
|
Sign up to set email alerts
|

Developmental exposure to silver nanoparticles at environmentally relevant concentrations alters swimming behavior in zebrafish (Danio rerio)

Abstract: Silver nanoparticles (Ag-NP) are ubiquitous in household and medical products because of their antimicrobial activity. A consequence of the high volume of Ag-NP production and usage is increased amounts of Ag-NPs released into the environment. Their small size (between 1–100 nanometers) results in unique physiochemical properties that may increase toxicity relative to their bulk counterpart. Therefore, the goal of this study is to assess the potential toxicity of environmentally relevant concentrations of Ag-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…One of the other goals of the current set of studies was to determine whether developmental exposure to NPs could affect gut microbiota populations from weaning to adulthood in mice. Our past studies with rats examined the effects of NPs on gut microbiota focused solely on direct effects 30 , 45 54 , 59 , 60 , 98 . However, to the best of our knowledge, no studies have examined whether in utero exposure to NPs might deleteriously affect the initial bacterial colonization of the gut that would lead to permanent changes on composition of the gut flora.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the other goals of the current set of studies was to determine whether developmental exposure to NPs could affect gut microbiota populations from weaning to adulthood in mice. Our past studies with rats examined the effects of NPs on gut microbiota focused solely on direct effects 30 , 45 54 , 59 , 60 , 98 . However, to the best of our knowledge, no studies have examined whether in utero exposure to NPs might deleteriously affect the initial bacterial colonization of the gut that would lead to permanent changes on composition of the gut flora.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies in zebrafish ( Danio rerio ), fruit flies ( Drosophila melanogaster ), and Mediterranean Sea urchins ( Arbacia lixula ) reveals that developmental exposure to AgNPs can lead to neurobehavioral alterations, gut-dysbiosis and other disturbances 45 54 . Select studies have also suggested that perinatal exposure to AgNPs can affect neurobehavioral programming and other offspring parameters in rodent models 36 , 43 , 55 57 , although more work is needed to understand the potential health effects in mammals of developmental exposure to such compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Also Klingelfus et al described neurotoxic effects of Ag NPs on neotropical fish (Hoplias intermedius) [126]. A Ag NPs caused hyperexcitability in developing zebrafish was reported far below concentrations found in some aquatic environment [127].…”
Section: Toxicity In Non-mammalian Vertebratesmentioning
confidence: 99%
“…At higher doses, the same research reports toxic effects in embryos and larvae, including bending in myotome, deformity in tail region, somites, notochord and swelling in anterior and posterior region of embryos and larvae (Sarkar et al, 2018). Embryos exposed after fertilization (4-120 hpf) at concentrations between 0.03 to 3 mg/L of AgNPs, showed hyperactivity but did not present dangers for hatching, morphology, or mortality (González et al, 2018). Adult zebrafish exposed to 10 µg/L of AgNPs reduced fertility and increased malformation prevalence in the embryos only after two weeks of exposure (Orbea et al, 2017).…”
Section: Silver Nanoparticlesmentioning
confidence: 98%